2021
DOI: 10.1111/eos.12797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zirconia surface modification using dopamine polymerisation on the shear bond strength of resin cement

Abstract: This study evaluated the influence of polydopamine treatment on the surface properties and bond strength of yttria‐stabilised tetragonal zirconia polycrystal (Y‐TZP). Sixty‐three zirconia blocks (10 × 10 × 2 mm) were randomly divided into three groups defined by surface treatment: (i) control group (C), (ii) grit‐blasted with 110 μm alumina particles (GB), and (iii) polydopamine (PDA) coating. The surfaces of specimens subjected to different treatments were investigated by X‐ray photoelectron spectroscopy (XPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Therefore, the failure mode is mixed (both cohesive fracture and adhesive fracture occurred, and some resin particles remain on the surface of the adhesive and zirconia). [ 35 ] From the part pointed by the arrow in Figure 6D, it can be seen that the filler particles are evenly distributed in the resin matrix. This is because the viscosity of Bis‐GMA is reduced after modification, and the formed resin matrix is loose, which is less dense than that before modification.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the failure mode is mixed (both cohesive fracture and adhesive fracture occurred, and some resin particles remain on the surface of the adhesive and zirconia). [ 35 ] From the part pointed by the arrow in Figure 6D, it can be seen that the filler particles are evenly distributed in the resin matrix. This is because the viscosity of Bis‐GMA is reduced after modification, and the formed resin matrix is loose, which is less dense than that before modification.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of dopamine and polydopamine was approved to augment the bioactivity of the zirconia surface and enhance cell adhesion over the surface. The enhancement is attributed to the easy adsorption processes taking place on the surfaces due to the strong anchoring of the catechol functionality [68]. This type of coating also reduces bacterial adhesion on the coated surface and improves antimicrobial activity, which aids in the rapid healing and regeneration of the soft tissues surrounding the dental implants.…”
Section: Polydopamine (Pda)mentioning
confidence: 99%
“…Additionally, PDA can be used as a cross-linking. A recent study that treated zirconia with PDA coating showed that PDA improved the bond strength between the resin cement and zirconia surface (98). The manufacture of PDA coating is easy-going and multi-functional.…”
Section: Polydopaminementioning
confidence: 99%